3D printed shelters for animals - Chia, Joven Kah Seng (2019)
This report details the mechanical design of an Animal Shelter which would be used in the housing of stray animals in Jurong Island. More specifically, it aims to act as a point that allows for users to have an easy-to-set-up and effective way to have control on the growing stray population in Jurong Island. Stray dogs have been a common sight in Jurong Island ever since it was officially opened back in October 2000. Stray dogs there has shown to have many negative impacts on the environment there as well as on human health, which can range from causing collisions when they run on the road, to the even bigger threat of spreading diseases like rabies as they were not vaccinated. A pilot project, namely the Trap-Neuter-Release-and-Manage (TNRM) programme, was launched in December 2014 as a partnership between JTC and various animal welfare groups, such as Noah’s Ark Cares (NAC) to control the population. Dogs are first captured, sterilised and then either released or adopted. While the programme has been effective, there has been issues with the helpers from NAC in trying to keep track of smaller packs in Jurong Island. The main objective of this project is to design a housing that is not only portable, easy to assemble, durable and will make the control of the pack population easier by acting as a place for the packs as housing. Comparison between existing devices will help determine which design will be most suitable. Force and Finite Element method analysis will help to determine the suitability of the design. A prototype of the design will also be built, with the use of 3D printing methods to help analyse the perks as well as any improvements to make the housing more efficient